SPECTRUM OF CULTURE POSITIVE HOSPITAL ACQUIRED PNEUMONIA IN PATIENTS RECEIVING PROTON PUMP INHIBITORS: Culture Positive Hospital Acquired Pneumonia - Khan, Aaqib Jahangir; Akhtar, Aftab (Pakistan Armed Forces Medical Journal, 2018)
Objective: To identify the spectrum of organisms in intensive care unit (ICU) in patients who were receivingproton pump inhibitors for stress ulcer prophylaxis and diagnosed as having hospital-acquired pneumonia(HAP).Study Design: Cross sectional study.Place and Duration of Study: Shifa International Hospital Islamabad, from Apr 2016 to Aug 2016.Material and Methods: One hundred and forty eight patients (134 receiving PPI’s and 14 not receiving) in MICUof Shifa International Hospital were included in this study. Hospital acquired pneumonia was defined as Newchest infiltrates developing within 48 hours of admission, Fever of greater than 38 degrees Celsius and totalleucocyte count of more than 11000 or less than 3500. In all patients tracheal cultures were followed at 24 and 48hours and microbiologic spectrum was defined.Results: Out of 148 patients admitted to ICU during the study period, 45 patients (33.6 percent) developed HAPin PPI group compared to 1 in non PPI group. The initial tracheal cultures at admission were negative. Out ofthe 45 patients who fulfilled criteria for HAP 40 patients (89%) had positive tracheal cultures for gram negativebacteria which included Acinetobacter, Klebsiella and Escheria species. The cultures remained negative for 5patients (11%) with HAP. The 89 patients who didn’t fulfill the criteria for HAP, 25 patients still had positivetracheal cultures but more than fifty percent of the cultures yielded Candida Albicans. In the non PPI group only1 patient developed HAP. HAP incidence was PPI group (p 0.042).Conclusion: Gram negative bacteria was prevailed as the causative organism in patients who developed hospitalacquired pneumonia (89 percent) and receiving proton pump inhibitors in medical intensive care unit withgreater number incidence of HAP in PPI group.